Editorial Introduction to the Special Section: Deconstructing Offshore Finance. (29th May 2015) - Clark, Gordon L.; Lai, Karen P. Y.; Wójcik, Dariusz
Abstract Recent scandals involving large corporations including Amazon, Apple, Google, Starbucks, and HSBC have highlighted the problems of tax avoidance, evasion, and offshore financial activities. Considering their significance to growing inequality and financial instability, renewed media and public attention is well justified, and new research on these topics urgent. At the same time, however, there is confusion in the very use of the term offshore finance. Some apply it interchangeably with tax havens; others go as far as to use it as a synonym of international finance. We argue that offshore finance needs a precise definition and careful positioning in a broader economic geographical framework. We suggest a definition based on the legal and accounting, in addition to financial, aspects of offshore finance, and we propose the concept of global financial networks to situate offshore jurisdictions and offshore finance in the firm–territory nexus and in relation to global production networks. This sets the stage for the three research articles presented in this issue, which map offshore financial networks at global and regional scales, and investigate their causes and mechanisms.